Subjective Measurements Analysis of Usability Evaluation for Deaf People Mobile Applications - Nathan, Shelena Soosay; Hussain, Azham; Hashim, Nor Laily (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Usability evaluation is an important element that will enable to identify performance of any system or application. Through identification of these issue, usefulness of a product can be improvised. Many usability models are available to evaluate the system usability. Usability data can be collected in two different method which is objective and subjective data. This paper present subjective data analysis of usability evaluation conducted with deaf people mobile application. The results show that the application evaluated having low satisfaction score for deaf people.